Acquired Fanconi Syndrome from Tenofovir Treatment in a Patient with Hepatitis B - Shirley X. Jiang; John Duncan; Hin Hin Ko (Case Reports in Hepatology)
Fanconi syndrome is a rare disease of generalized proximal tubule dysfunction which can be acquired secondary to certain medications, including tenofovir, a commonly used hepatitis B treatment. Signs and symptoms of ensuing renal wasting can be severe but vague, leading to potentially avoidable invasive investigations and delays in diagnosis. We present a case of a 62-year-old female with chronic hepatitis B on tenofovir treatment who was found to have subacute weakness, anorexia, and weight loss. She underwent extensive investigations including computed tomography (CT) imaging, bronchoscopy, upper and lower endoscopy, and psychiatric evaluation. Finally, persistent electrolyte derangements led to urine studies, which demonstrated acquired Fanconi syndrome secondary to tenofovir. After discontinuing tenofovir disoproxil fumarate and starting tenofovir alafenamide, her symptoms resolved and her renal function recovered. This case illustrates the importance of maintaining clinical suspicion for tenofovir-induced Fanconi syndrome, given the common use of tenofovir as first-line hepatitis B treatment and the availability of less nephrotoxic alternatives.